1991
DOI: 10.1002/kin.550230508
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation reactions between alkyl and fluoroalkyl radicals. VI. Difluoromethyl and n‐propyl radicals

Abstract: Cross-disproportionation to combination ratios for CF2H and n-C3H7 radicals have been determined (the hydrogen acceptor radical is given first) to be A(n-C3H7,CF2H) = 0.30 2 0.01 and A(CF2H, n-C3H7) = 0.057 ? 0.006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…The donor radical contains a CF 3 group at the ␣-carbon and this electronrich substituent may repel an incoming CF 3 acceptor radical, but not a CF 3 CH 2 CHCH 3 radical that has a greater hydrocarbon-radical character. A similar trend has been observed by Pritchard and coworkers [16][17][18][19][20]. For example, when the donor radical was CHF 2 and the acceptor radical was changed from a perfluoro radical to an alkyl radical, k d /k c , for several acceptor radicals, varied as follows: 0.088 (CF 3 ), 0.072 (n-C 3 F 7 ), 0.07 (CHF 2 ), 0.06 (CH 2 F), 0.35 (CH 3 ), 0.37 (C 2 H 5 ), and 0.30 (n-C 3 H 7 ).…”
Section: Figuresupporting
confidence: 88%
See 1 more Smart Citation
“…The donor radical contains a CF 3 group at the ␣-carbon and this electronrich substituent may repel an incoming CF 3 acceptor radical, but not a CF 3 CH 2 CHCH 3 radical that has a greater hydrocarbon-radical character. A similar trend has been observed by Pritchard and coworkers [16][17][18][19][20]. For example, when the donor radical was CHF 2 and the acceptor radical was changed from a perfluoro radical to an alkyl radical, k d /k c , for several acceptor radicals, varied as follows: 0.088 (CF 3 ), 0.072 (n-C 3 F 7 ), 0.07 (CHF 2 ), 0.06 (CH 2 F), 0.35 (CH 3 ), 0.37 (C 2 H 5 ), and 0.30 (n-C 3 H 7 ).…”
Section: Figuresupporting
confidence: 88%
“…Pritchard and coworkers [17] also found that hydrocarbon acceptor radicals have much larger k d /k c ratios than perfluorocarbon radicals. As mentioned previously, Pritchard and coworkers [16][17][18][19][20] found that methyl, ethyl, and n-propyl radicals, accepting an H from CHF 2 , all had k d /k c near 0.3, whereas the k d /k c values were between 0.06 and 0.09 when the acceptor radical was a n-C 3 F 7 or a CF 3 radical.…”
Section: Figurementioning
confidence: 66%
“…(In using the symbol A for cross-disproportionation reactions the hydrogen acceptor radical is given first.) On the other hand when alkyl radicals interact with CFzH radicals, unexpectedly high values for the transfer of the H-atom from the CF2H to the alkyl radical have been found, e.g., A(CzH5, CFzH) = 0.33 % 0.04, the average of three determinations [1,4], and A(n-C3H7, CF2H) = 0.30 -+ 0.01 [5]. The alternative crossdisproportionation pathways that produce CF2H2 and alkene show what appear to be much more predictable values [5]; a tabulation is given later.…”
Section: Introductionmentioning
confidence: 96%
“…Calibrations were made with commercially available samples, except for C2F4H2 and C4FgH. The C2F4H2 was prepared by TFA photolysis [5], and C4F10 was used for the cross-product C4F9H, with a minor correction based on the change in sensitivities exhibited by C4H10, C2F5C2H5 and C4F10. (The pentafluorobutane was intermediate between the other two butanes and the small correction was marginally greater than the experimental error in the C4F10 calibration).…”
Section: Introductionmentioning
confidence: 99%